Isomer separation and analysis of amphiphilic polysialogangliosides using reversed‐phase liquid chromatography‐mass spectrometry. Issue 9 (8th March 2021) - Park, Jun Young; Shrestha, Sarmila Amatya; Cha, Sangwon
Abstract: Gangliosides are amphiphilic, acidic glycosphingolipids possessing one or more sialic acid residues and several isobaric structural isomers with different abundances and bioactivities. Therefore, the distinction between these isomers is crucial for their proper profiling. Although liquid chromatography–mass spectrometry has been successfully employed for this purpose, the distinction process can still be improved, particularly regarding liquid chromatography. Recently, a reversed‐phase liquid chromatography method that could separate disialoganglioside isomers was reported; however, the distinction of trisialoganglioside isomers using reversed‐phase liquid chromatography has not been demonstrated. Here, we investigated the practicality of a reversed‐phase liquid chromatography with an octadecylsilane column for separating polysialoganglioside isomers and successfully achieved the isomer separation of disialogangliosides and trisialogangliosides for the first time. We also confirmed several crucial factors in the mobile‐phase composition, which affect the differential retention and mass spectral response of the isomers. First, an organic modifier, acetonitrile, exhibited superior selectivity against polysialogangliosides over methanol. Second, ammonium bicarbonate was the best ammonium salt additive among those tested, in terms of the separation efficiency and mass spectral response. Third, as the ammonium salt concentration increased, the negative electrospray ionization response was extensively suppressed, and the retention of gangliosides increased.